Probing local surface reactivity with hydrogen molecules - Realizing an atom/molecule scanning probe - Dino, Wilson Agerico (Animo Repository, 2003)
We explore the feasibility of using hydrogen to probe local surface reactivity. To do this, we compare the dissociation dynamics of H 2/Cu3Pt(111)[12̄1] and H2/NiAl(110) [11̄0]. Calculation results show that the corresponding adsorption/sticking probability S vs. incidence translational energy Et profile changes with the apparent surface features. The results not only indicate that hydrogen is sensitive to the local features of the surface it is interacting with, but it is also able to distinguish among them. These discernible differences turn up as measurable/observable quantities verifiable with current experimental techniques.